Photochemically Active Fluorophore–DNA/RNA Conjugates for Cellular Imaging of Nucleic Acids by Readout in Electron Microscopy. Issue 4 (21st June 2013) - Holzhauser, Carolin; Kracher, Sabrina; Rubner, Moritz M.; Schmucker, Wolfgang; Wagenknecht, Hans‐Achim; Witzgall, Ralph
<x xml:space="preserve">Abstract</x> A two‐way street: The photochemically active chromophore–nucleic acid conjugates presented herein allow not only imaging by fluorescence microscopy but additionally are able to photoinduce 3, 3′‐diaminobenzidine (DAB) polymerization for staining to enable additional readout with electron microscopy.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>